The Mediator Role of Academic Resilience in the Relationship of Anxiety Sensitivity, Social and Adaptive Functioning, and School Refusal With School Attachment in High School Students - Seçer, İsmail; Ulaş, Sümeyye (Frontiers in Psychology, 2020)
The school has an important function in providing the environment for young people to acquire many skills and knowledge required by contemporary life, but the problems of attachment to the school and problematic attendance all over the world reveal an increasing statistic. It is thought that some negative processes such as anxiety sensitivity, social and adaptive functioning and school refusal can affect this problem. On the other hand, it is considered that the academic resilience of young people has an important protective function in terms of this risk factors. For this purpose, the mediator role of academic resilience between anxiety sensitivity, social and adaptive functioning and school refusal and school attachment were examined in the Turkish sample of 452 high school students. In the process of data collection, the school refusal assessment scale, social and adaptive functioning scale, and academic resilience scale were adapted and used in the Turkish culture. In the data analysis, the structural equation model was used to determine the direct and indirect predictive effects between the variables. The results of the study showed that academic resilience fully mediated the relationship between anxiety sensitivity and school attachment, whereas it partially mediated the relationship between social and adaptive functioning and school refusal and school attachment. Based on the results of the study, it was evaluated that high academic resilience has a strong protective function against the problems of negative school attachment and problematic school absenteeism among young people and this finding was discussed within the context of literature